2020
DOI: 10.3390/ma13214821
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Solution Plasma Processing for the Production of Chitosan/Ag Composites with the Antibacterial Effect

Abstract: The development of novel biocompatible and biodegradable materials for medical applications has been drawing significant interest in the scientific community for years. Particularly, chitosan loaded with silver nanoparticles (Ag NPs) has a strong antimicrobial potential and could be applied, for example, as wound dressing material. In this work, chitosan/Ag NP composites were produced utilizing a single-step plasma-solution process, which is simple and environmentally friendly. An acetic solution of chitosan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…However, for some ions, such as Zn 2+ and Mn 2+ ions, coordination is possible only with the participation of amino groups, either according to the “bridge” model or to the “pendant” model [ 112 , 128 ]. Similar, Ag ions can be used to obtain chitosan-Ag nanocomposites, which present remarkable antibacterial activity [ 129 , 130 , 131 , 132 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for some ions, such as Zn 2+ and Mn 2+ ions, coordination is possible only with the participation of amino groups, either according to the “bridge” model or to the “pendant” model [ 112 , 128 ]. Similar, Ag ions can be used to obtain chitosan-Ag nanocomposites, which present remarkable antibacterial activity [ 129 , 130 , 131 , 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesizing of metal nanoparticles (e.g., AgNPs) in a chitosan matrix to form nano-biocomposites for biomedical applications is one of the achievements of the last decade [ 130 , 131 , 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms can grow, forming biofilms on surface of some biomaterials [94]. We observed that (Figure 10) PLGA, without silver oxide nanoparticles, did not affect E. coli growth.…”
Section: Discussionmentioning
confidence: 85%
“…In a similar study, Titov et al prepared chitosan/AgNPs composite foils and characterized their morphology by backscattered imaging. 24 As shown in Figure 9, AgNPs were well distributed (bright dots), and a smooth surface was obtained. Additionally, partially agglomeration of AgNPs can be detected.…”
Section: Morphological Characterization Of Bionanocompositesmentioning
confidence: 84%